Resilient cooperative control for optimal current sharing and voltage regulation of microgrid-based distribution network under FDI attacks - Wang, Biheng (Frontiers in Energy Research, 2022)
In this study, the security secondary control problems are considered for optimal current sharing and voltage restoration of a microgrid distribution network under false data injection (FDI) attacks. To solve these problems, a resilient secondary control method is provided. Specifically, a resilient secondary controller is designed by introducing an adaptive parameter based on the adaptive technique. Then, a theoretical analysis method is provided to show that the designed resilient secondary controller can ensure optimal current sharing and voltage regulation under FDI attacks.